Development of Indonesian Language Learning Videos Based on a Scientific Approach to Poetry Materials - Luckyani Gulo Telaumbanua; Noveri Amal Jaya Harefa; Imansudi Zega (Universitas Muhammadiyah Enrekang, 2022)
The purpose of this research is to develop an Indonesian language learning video based on a scientific approach that is feasible, practical and effective. This type of research is development research using the ADDIE model consisting of analysis, design, development, implementation, and evaluation. The types of data obtained in this study are quantitative and qualitative data. The research instruments used in this development research are validation sheets, practicality questionnaires for learning videos, and learning outcomes tests for assessing the effectiveness of learning videos. The research results show that learning videos developed based on the Scientific approach are feasible, practical, and effective to use to meet the research's expectations or objectives. Thus, the researchers suggest, namely: 1) Indonesian language education subject teachers at SMA Negeri 1 Gunungsitoli can use this learning video as one of the learning media to improve the quality of learning and as a learning strategy. 2) make the results of this research as additional knowledge in utilizing IT. Further researchers should use this researcher as additional insight in carrying out research.